2010
DOI: 10.1097/coh.0b013e328333850f
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to reduce early morbidity and mortality in adults receiving antiretroviral therapy in resource-limited settings

Abstract: Purpose of review We review recently published literature concerning early morbidity and mortality during antiretroviral therapy (ART) among patients in resource-limited settings. We focus on articles providing insights into this burden of disease and strategies to address it. Recent findings In sub-Saharan Africa mortality rates during the first year of ART are very high (8%-26%), with most deaths occurring in the first few months. This compares to 3%-13% in programmes in Latin America and the Caribbean and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 62 publications
3
74
0
Order By: Relevance
“…Similar findings were noted in a communitybased study in Zimbabwe: duration of infectiousness prior to TB diagnosis was 18 weeks for HIV-1 infected versus 1 yr for HIV-1 uninfected patients [49]. TB may also present as an acute community acquired pneumonia and needs to be considered in any HIV-1 infected patient presenting with acute respiratory illness (table 1) [50,51].…”
Section: Rapid Progression and Higher Mortalitysupporting
confidence: 55%
“…Similar findings were noted in a communitybased study in Zimbabwe: duration of infectiousness prior to TB diagnosis was 18 weeks for HIV-1 infected versus 1 yr for HIV-1 uninfected patients [49]. TB may also present as an acute community acquired pneumonia and needs to be considered in any HIV-1 infected patient presenting with acute respiratory illness (table 1) [50,51].…”
Section: Rapid Progression and Higher Mortalitysupporting
confidence: 55%
“…This finding suggests that treating depression at ART initiation as previously recommended (Jia et al, 2005) may be indicated in this South African population. The results draw attention to the need for early HIV diagnosis, increased access to ART services with earlier treatment initiation, routine screening and aggressive management of opportunistic infections, particularly tuberculosis (Lawn, Harries & Wood, 2010;Macpherson et al, 2008). Differences in health status (lower CD4 cell counts and higher depression scores) should be taken into account when initiating patients on ART.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated this study would serve as a baseline to measure future progress, a first step to fill in many gaps in the information about medical care of people living of HIV/AIDS in the KSA. Thus, we hope, through further future similar work in the area of HIV medical care, to inform providers to standardize care, reduce morbidity and mortality, monitor and reduce resistance to ART, and ultimately improve the quality of life for those living with HIV/AIDS [11][12][13].…”
Section: Introductionmentioning
confidence: 99%